DETERMINANTS OF SECOND-DOSE MEASLES IMMUNIZATION ACCEPTANCE AMONG TODDLERS: A SYSTEMATIC LITERATURE REVIEW - Anita Dewi Anggraini; Diyas Windarena Anggraini; Dwi Ardani Rochmaniah Anggraini; Ika Ayu Purnamasari Anggraini (Nurse and Health: Jurnal Keperawatan, 2026)
Background: Measles is a contagious disease with high morbidity and mortality rates. Globally, measles immunization coverage has reached 81% for the first dose and 71% for the second dose. In Southeast Asia, the coverage is 91% for the first dose and 85% for the second dose; however, these figures remain below the measles elimination target. Purpose: identify the factors influencing second-dose measles immunization coverage. Methods: The method used is a Systematic Literature Review with keywords formulated based on the PICO framework: Population: “children,” Exposure: “second-dose measles vaccine,” and Outcome: “associated factors,” “predictors,” or “determinants.” From a total of 1,159 articles identified, ten studies met the inclusion criteria and were analyzed further. Results: The results show that second-dose measles immunization coverage is influenced by several factors, including maternal age, education level, knowledge, utilization of maternal health services, and accessibility to healthcare facilities. Maternal health service utilization, such as antenatal care visits, delivery at health facilities, and postnatal checkups, significantly increases the likelihood of children receiving the second dose. Conversely, barriers such as long distances, limited transportation, and long waiting times remain major challenges. Conclusion: Therefore, strengthening education, integrating maternal health services with immunization programs, and expanding access in remote areas are essential to improving measles immunization coverage. These efforts provide an important foundation for formulating more effective policies to support both global and national measles elimination strategies.